2015
DOI: 10.7759/cureus.273
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Use of Personalized Video Recordings to Improve Neurosurgical Patient-Provider Communication

Abstract: Background: Providing patients with a video recording of their visit with a medical professional is a common-sense method for improving patient-provider communication.Objective: To describe the patient and provider experiences to video recording clinical medical encounters and providing the patient with a copy of the video for informational purposes.Methods: Since 2009, over 2,800 patients of eight different neurosurgeons chose to be video recorded during their encounter with the doctor and were provided acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 41 publications
(33 reference statements)
0
48
0
1
Order By: Relevance
“…Yet a handful of clinics in the US are taking a proactive approach 2. A cancer clinic in Texas offers patient digital recorders to capture their visit information,6 and a neurological institute offers patients video recordings of their visits that are accessible on a secure website 7. One doctor in Michigan has been offering to record clinical encounters since 2011 8…”
mentioning
confidence: 99%
“…Yet a handful of clinics in the US are taking a proactive approach 2. A cancer clinic in Texas offers patient digital recorders to capture their visit information,6 and a neurological institute offers patients video recordings of their visits that are accessible on a secure website 7. One doctor in Michigan has been offering to record clinical encounters since 2011 8…”
mentioning
confidence: 99%
“…Sin embargo, las videograbaciones permiten una valoración en profundidad de cada entrevista sin alterar el transcurso de la misma, siendo un recurso docente habitual empleado en la formación de posgrado4, 9, 27, 28. Además, diferentes autores5, 29, 30 no encuentran cambios en los comportamientos de los residentes ni en la duración o la calidad de la consulta, permitiendo comprobar el desempeño habitual en la atención a pacientes reales. El sesgo de información se trató de resolver con la formación previa de los evaluadores externos y el uso de un cuestionario validado 14 .…”
Section: Discussionunclassified
“…Johnson et al . found no differences between standard written information, standard information plus video, and standard information and video, plus formal nurse‐taught education . Rather than just using standardized video, few studies have examined the impact of individualized audio and video recordings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies that have explored the use of clinic recordings have found no increased risk of malpractice suits with personalized recorded videos . In fact, Meeusen and Porter previously published their experience with recording 2100 videos in high‐risk neurosurgery specialty without a single legal challenge from patients relating to or involving the video recording.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation